2015
DOI: 10.1038/srep14474
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen mediates neuroprotection on hippocampal CA1 pyramidal cells through the regulation of autophagy under chronic cerebral hypoperfusion

Abstract: GABA receptors play an important role in ischemic brain injury. Studies have indicated that autophagy is closely related to neurodegenerative diseases. However, during chronic cerebral hypoperfusion, the changes of autophagy in the hippocampal CA1 area, the correlation between GABA receptors and autophagy, and their influences on hippocampal neuronal apoptosis have not been well established. Here, we found that chronic cerebral hypoperfusion resulted in rat hippocampal atrophy, neuronal apoptosis, enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 90 publications
(126 reference statements)
9
80
0
Order By: Relevance
“…Baclofen, a GABABR agonist, improved the down-regulation of GABABR2 expression associated with cognitive impairment and special working memory impairment , while also reversed neuronal damage with autophagy regulation under chronic cerebral hypoperfusion (Liu et al, 2015). Similar to our synaptic results, AP2-associated protein kinase 1 (AAK1) expression was significantly reduced in the hippocampal CA1 region under chronic cerebral hypoperfusion, which could be restored by baclofen to the control level (Li et al, 2014) (Fig.…”
Section: Chronic Cerebral Hypoperfusion Effects On Gabaergic / Glutamsupporting
confidence: 85%
“…Baclofen, a GABABR agonist, improved the down-regulation of GABABR2 expression associated with cognitive impairment and special working memory impairment , while also reversed neuronal damage with autophagy regulation under chronic cerebral hypoperfusion (Liu et al, 2015). Similar to our synaptic results, AP2-associated protein kinase 1 (AAK1) expression was significantly reduced in the hippocampal CA1 region under chronic cerebral hypoperfusion, which could be restored by baclofen to the control level (Li et al, 2014) (Fig.…”
Section: Chronic Cerebral Hypoperfusion Effects On Gabaergic / Glutamsupporting
confidence: 85%
“…It has been reported that the upregulation of GABA B receptor activity could inhibit NMDA-receptor-mediated nitric oxide (NO) production by neuronal NO synthase (nNOS) in brain ischemic injury (Zhou et al, 2008). Recent studies have revealed that, under chronic cerebral hypoperfusion, the effects of GABA B receptors activated by baclofen could reverse neuronal damage by increasing the activation of Akt, GSK-3β and ERK and upregulating the bcl-2/bax ratio, which suppress cytodestructive autophagy (Liu et al, 2015). Another study has shown that baclofen markedly improves memory impairment and alleviates neuronal damage in chronic ischemic rats by increasing the expression and regulating the function of the TPR-containing Rab8b-interacting protein (TRIP8b; Li et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that autophagy is essential for cells in response to fluctuating environments during acute ischemia or CCH. For example, the level of LC3 is increased at 2 or 5 weeks after CCH [8,9]. In addition, the levels of LC3 and beclin-1 and the number of autophagosomes are increased at 8 weeks after 2VO surgery.…”
Section: Discussionmentioning
confidence: 85%
“…For example, the accumulation of autophagic vacuoles and elevated microtubule-associated protein 1 light chain 3 (LC3) levels were found in the cortex of 2VO rats at 2 weeks after surgery [8]. Liu et al reported that the level of LC3 was significantly increased in both the cortex and hippocampal CA1 area of 2VO rats at 5 weeks after surgery, and GABA receptors reversed the neuronal damage by activating autophagy [9]. These studies suggested that autophagy may play a critical role in CCH-induced brain damage.…”
Section: Introductionmentioning
confidence: 99%